Application of the growth accounting method for the construction industry - Lankauskienė, Toma (Journal of Business Economics and Management, 2016)
As the growth accounting method can suggest research benefits, this paper is dedicated to the application of the method in the construction industry. The lack of methodologies for the application of the method in the less developed countries has necessitated the design of the methodology presented in the paper. Once the methodology is composed, comparable results can be obtained on the fulfilment of international academic standards. The paper presents the main methodological problems faced by the author while working on the problem. In addition, it enables the identification of the proximate sources of growth as well as the performance of economic analysis from a comparative perspective of countries at different stages of development. The scientific merit of the paper – the entire group of intangible capital rather than only software will correspond to knowledge based capital. The results suggest that Lithuania is in a rather strong position in terms of productivity growth, but the same could not be said when considering the structure of its main determinants compared with the more developed countries.First published online: 02 May 2016